2018
DOI: 10.1088/1741-4326/aaaf26
|View full text |Cite
|
Sign up to set email alerts
|

Fast-ion stabilization of tokamak plasma turbulence

Abstract: A significant reduction of the turbulenceinduced anomalous heat transport has been observed in recent studies of magnetically confined plasmas in the presence of a significant fastion fractions. Therefore, the control of fastion populations with external heating might open the way to more optimistic scenarios for future fusion devices. However, little is known about the parameter range of relevance of these fastion effects which are often only highlighted in correlation with substantial electromagnetic fluctua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
144
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 70 publications
(156 citation statements)
references
References 29 publications
11
144
0
Order By: Relevance
“…A particularly interesting example is the recent experimental and numerical evidence suggesting a link between the presence of fast ions and substantial improvement of energy confinement in predominantly ITG (ion-temperature-gradient) driven turbulence [1][2][3][4][5]. Dedicated theoretical studies have already identified a number of possible energetic ion effects on plasma turbulence like dilution of the main ion species [1], Shafranov shift stabilization [6] and resonance interaction with bulk species micro-instabilities in certain plasma regimes [7]. They furthermore contribute to the total plasma pressure and increase the kinetic-tomagnetic pressure ratio, β, which is a measure for the relevance of electromagnetic fluctuations, known to stabilize ITG modes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A particularly interesting example is the recent experimental and numerical evidence suggesting a link between the presence of fast ions and substantial improvement of energy confinement in predominantly ITG (ion-temperature-gradient) driven turbulence [1][2][3][4][5]. Dedicated theoretical studies have already identified a number of possible energetic ion effects on plasma turbulence like dilution of the main ion species [1], Shafranov shift stabilization [6] and resonance interaction with bulk species micro-instabilities in certain plasma regimes [7]. They furthermore contribute to the total plasma pressure and increase the kinetic-tomagnetic pressure ratio, β, which is a measure for the relevance of electromagnetic fluctuations, known to stabilize ITG modes.…”
Section: Introductionmentioning
confidence: 99%
“…Our study is based on the JET-like scenario with deuterium, electrons and externally injected neutral beam deuterium described in detail in Ref. [7,16], with a reduced safety factor of q = 1. and the minimum k y ρ s = 0.025 with thermal gyroradius ρ s = (T e /m i ) 1/2 /Ω i . Here, Ω i = m i c/qB 0 denotes the gyro-frequency, T i the main ion temperature, m i the main ion mass, q the charge, B 0 the magnetic field on axis and c is the speed of light.…”
Section: Introductionmentioning
confidence: 99%
“…It reads as The same AUG shot has been simulated in GENE in case with adiabatic electrons (one can see also Ref. 47 ), using the flux-tube version of the code at s = 0.5. In Fig.…”
Section: Comparison With Genementioning
confidence: 99%
“…From the energy relation of Eq. 111 it is to compute the more unstable linear growth rate γ through the time variation of the potential energy, as shown in details in Ref47,56,58,59 , by removing the sum over all the species and studying each term separately. Positive (negative) values of ∂E k,s /∂t indicate that the plasma species considered is giving (taking) energy to (from) the electrostatic field component with a consequent growth (damping) of the mode.…”
mentioning
confidence: 99%
“…Recent results [9] indicate that an electrostatic mechanism, related related to a wave-fast particle resonant interaction [10,11], can also play an important role in the stabilization of ITG modes in some conditions. The study in ref.…”
Section: Introductionmentioning
confidence: 99%